Phenomenology of Muslim Families Facing Digital Challenges in Children’s Moral Development - Ihsan, Prima Maulana; Maksum, Muh. Nur Rochim (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study aimed to explore the experiences of Muslim families in facing digital challenges and their impact on children’s moral development. The advancement of digital technology has provided significant benefits in education, communication, and entertainment; however, it has also posed risks such as reduced parental control, exposure to inappropriate content, and the weakening of moral guidance. This research employed a qualitative approach with a phenomenological design. The participants consisted of six Muslim parents with children aged between 8 and 15 years in Al-Abidin Karanganyar. Data were collected through in-depth interviews and supported by observations, then analyzed thematically to identify patterns of experiences and parenting strategies. The findings revealed that parents experienced dilemmas in utilizing technology as an educational tool while also needing to anticipate its negative impacts. The main strategies implemented included limiting the duration of gadget use, providing close supervision, maintaining open communication between parents and children, and strengthening religious values within the family environment. The most common challenges faced were limited digital literacy among parents and the strong influence of peer groups on children’s behavior. This study concludes that the digital challenges faced by Muslim families are multidimensional, encompassing technical, social, and moral aspects. Therefore, collaboration among families, schools, and communities is essential to strengthen digital literacy that aligns with Islamic values. Such efforts will enable children to grow as technologically literate individuals with strong moral character.